Corporate Energy Management Disclosure : Empirical Evidence from Indonesia Stock Exchange - Meiryani, Meiryani; Huang, Shi-Ming; Lindawati, A. S. L.; Purnomo, Agung; Fahlevi, Mochammad; Salim, Gazali (International Journal of Energy Economics and Policy, 2023)
Energy is one of the vital needs for humans. Indonesia as a developing country faces problems in ensuring the availability of energy. The aim of this research is to explore the development of practice energy management disclosure in accordance with GRI 302 (energy) in energy sub-sector companies listed on the Indonesia Stock Exchange (IDX) through disclosures issued by each company. This study uses secondary data collected from reports published by energy sub-sector companies listed on the Indonesia Stock Exchange (IDX) and can be accessed online. Data analysis was carried out using the data analysis model of Miles and Huberman (1992), namely data reduction, data presentation, drawing conclusions, and verification. The results of this study indicate that only thirty-six out of 74 energy subsector companies (49%) report energy management disclosure according to GRI 302 (energy) for three consecutive years (2020-2022). Nineteen out of thirty-six companies attach a GRI Index Reference to their GRI 302 (energy) reports. Meanwhile, the other thirty-eight companies did not attach the GRI Index Reference in their reports. The company is expected to develop a power plant that uses renewable energy as its energy source. By using renewable energy, companies can reduce consumption of non-renewable energy, and play a role in reducing CO2 emissions in the environment.